DEGRADASI LIMBAH TEKSTIL MENGGUNAKAN JAMUR LAPUK PUTIH Daedaleopsis eff. confragosa - Ngurah Mahendra Dinatha (Bumi Lestari Journal of Environment, 2013)
AbstractThe objectives of this research are to determine the optimum conditions (pH, concentrationof fungi, and incubation period) of degradation of textile dyeing waste using Daedaleopsiseff. confragosa and to determine the quality of the processed waste based on the parametersof chemical oxygen demand (COD), biological oxygen demand (BOD), total suspendedsolids (TSS), pH, and its color. The fungi was collected from a plantation areal in Negara,Bali and the untreated waste itself was also collected from a home textile dyeing industry inNegara, Bali. After rejuvenation process of the fungi, the optimum conditions were obtainedby collecting the COD data at various pH (4 - 10) and concentration of fungi (3% - 9%).Wefound that the degradation will be optimally progressing at pH 4 and fungi concentrationof 6%. Finally, the optimum period of degradation was determined by varying the incubationday from 0 - 12 days at optimum conditions. The optimum incubation period was 9 days. Thetreatment of the dyeing waste with fungi can decrease the level of the color, TSS, COD andBOD5 up to 81.05%, 70.21%, 85.17%, and 74.09% respectively.